Crystal structure of bis[4-(1H-pyrrol-1-yl)phenyl] ferrocene-1,1′-dicarboxylate: a potential chemotherapeutic drug - Pérez, Wanda I. (Acta Crystallogr E Crystallogr Commun, 2015)
The title iron(II) complex, [Fe(C(16)H(12)NO(2))(2)], crystallizes in the orthorhombic space group Pbca with the Fe(2+) cation positioned on an inversion center. The cyclopentadienyl (Cp) rings adopt an anti conformation in contrast with other substituted ferrocenes in which the Cp rings appear in a nearly eclipsed conformation. The Cp and the aromatic rings are positioned out of the plane, with a twist angle of 70.20 (12)°, and the C(Cp)—C(CO) bond length is shorter than a typical C—C single bond, which suggests a partial double-bond character and delocalization with the Cp π system. The structure of the complex is compared to other functionalized ferrocenes synthesized in our laboratory.